Pengaruh Pengaruh Sosial dan Psikologis Terhadap Keputusan Pembelian Pada Kain Songket Palembang - Oktaviani, Nikita; ., Megawati (MDP Student Conference, 2025)
This consider points to analyze the impact of social and mental variables on obtaining choices on Palembang songket cloth. The test of this ponder comprised of 252 respondents chosen utilizing the purposive examining strategy. Information were collected through a survey with a Likert scale and analyzed utilizing numerous direct relapse with the assistance of SPSS form 25. The comes about appeared that social and mental components had a critical impact on acquiring choices both in part and at the same time. This finding demonstrates that the social environment and mental components of buyers play an critical part in deciding obtaining choices for songket cloth